Peningkatan Ketrampilan Kreativitas Desain Grafis Digital Siswa SMU Menggunakan Aplikasi CANVA pada Ponsel Pintar - Fetty Tri Anggraeny; Henni Endah Wahanani; Fawwaz Ali Akbar; Mohamad Ilham Prasetyo Raharjo; Sandy Rizkyando (Universitas Islam Indonesia, 2021)
During the COVID-19 pandemic, teaching and learning activities must be carried out online from home. The development of technology today really helps the online teaching and learning process, there are many tools / software that can be used. Tools / software commonly used in online teaching and learning activities are Ms. Word, Ms. Power Point, and Virtual Lab. Another impact of technological developments coupled with pandemic conditions has led to more interactions between humans being carried out online through internet intermediaries on cellphones or computers. Currently cellphones do not only function as a medium of communication, some work that was previously completed using a computer / laptop can now be completed using a smart phone. So that cellphones can be used for more positive activities and support the teaching and learning process, sharing is carried out with students through sharpening design creativity through mobile applications on smart phones. In this activity, students hone graphic design skills using the CANVA application to support the teaching and learning process. The enthusiasm of students is quite high, as evidenced by the work produced in the form of personal profile designs, extracurricular activities and logos. Students can practice well the material presented. The school welcomes this activity, and wants to form an extracurricular Graphic Design at SMA Dharma Wanita so that it becomes a forum for student creativity in graphic design.